2016
DOI: 10.1186/s40170-016-0160-x
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition induction is associated with augmented glucose uptake and lactate production in pancreatic ductal adenocarcinoma

Abstract: BackgroundPancreatic ductal adenocarcinoma (PDAC) is a common malignancy with dismal prognosis. Metastatic spread and therapeutic resistance, the main causes of PDAC-related mortalities, are both partially underlined by the epithelial-mesenchymal transition (EMT) of PDAC cells. While the role of Warburg metabolism has been recognized in supporting rapid cellular growth and proliferation in many cancer types, less is known about the metabolic changes occurring during EMT, particularly in the context of PDAC.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 57 publications
4
59
0
Order By: Relevance
“…1Eiii); therefore, the rate of acid injection by photolysis at the hypoxic core (J inj ) can be estimated from the product of pH i change and b i , integrated across the spheroid. J inj was thus calculated to be 20.6 6 1.2 mM/min over the 4-min uncaging protocol, which is within the range of lactic acid production rates reported in PDAC cells (6,7). Repeating this uncaging protocol in spheroids superfused with CO 2 /HCO 3 2 buffer resulted in a substantially reduced [H + ] i response (Fig.…”
Section: Spheroidal Tissue Growths Show Radial Gradients Of Oxygen Tesupporting
confidence: 65%
See 2 more Smart Citations
“…1Eiii); therefore, the rate of acid injection by photolysis at the hypoxic core (J inj ) can be estimated from the product of pH i change and b i , integrated across the spheroid. J inj was thus calculated to be 20.6 6 1.2 mM/min over the 4-min uncaging protocol, which is within the range of lactic acid production rates reported in PDAC cells (6,7). Repeating this uncaging protocol in spheroids superfused with CO 2 /HCO 3 2 buffer resulted in a substantially reduced [H + ] i response (Fig.…”
Section: Spheroidal Tissue Growths Show Radial Gradients Of Oxygen Tesupporting
confidence: 65%
“…In contrast, if lactate were catabolized or exported by an H + -independent mechanism [e.g., via connexin43 channels (23)], a greater secondary active transport flux would be necessary. J met was taken to be 15 mM/min, the midpoint of the range of lactate production rates measured in PDAC cells (6,7). To calculate J leak , passive membrane permeability to H + ions (P H ) was measured in Colo357 cells (radius 8.78 6 0.08 mm, surface area:volume ratio r = 0.342 mm 21 ) that were dissociated from monolayers and superfused with solutions that block endogenous lactic acid production (glucose replaced with galactose) and inhibit membrane pH-regulatory transport (Cl 2 replaced with gluconate, CO 2 /HCO 3 2 replaced with HEPES, and 30 mM DMA added to block Na + /H + exchange).…”
Section: Spheroidal Tissue Growths Show Radial Gradients Of Oxygen Tementioning
confidence: 99%
See 1 more Smart Citation
“…EMT is a reversible phenomenon that allows epithelial cells to become motile and invade adjacent tissues to enter the circulation, and is an important mechanism by which carcinoma cells are thought to acquire metastatic potential (Ye and Weinberg, 2015). Moreover, a growing body of evidence has shown that the Warburg effect, a phenomenon wherein cells upregulate glycolysis while downregulating oxidative phosphorylation, is a metabolic adaptation exhibited by many cancer cells that becomes indispensible during these initial steps of metastasis (Dong et al, 2013; Liu et al, 2016). The Warburg effect allows cells to maintain ATP levels and reduce reactive oxygen species (ROS) production, allowing them to avoid anoikis, a form of cell death associated with loss of anchorage, as they enter the circulation (Kamarajugadda et al, 2012; Lu et al, 2015).…”
Section: Metabolic Reprogramming: Different Flavors Depending On Tumomentioning
confidence: 99%
“…Total RNA from jejunum and ileum samples was isolated from liquid nitrogen frozen and ground tissues with TRIZOL regent (Invitrogen, USA) and then treated with DNase I (Invitrogen, USA) [21-23]. The reverse transcription was conducted at 37°C for 15 min, 95°C 5 sec.…”
Section: Methodsmentioning
confidence: 99%